Development of Injectable Thermosensitive Chitosan-Based Hydrogels for Cell Encapsulation - Antonella Stanzione; Alessandro Polini; Velia La Pesa; Alessandro Romano; Angelo Quattrini; Giuseppe Gigli; Lorenzo Moroni; Francesca Gervaso (Applied Sciences, 2020)
The three-dimensional complexity of the native extracellular matrix (ECM) suggests switching from 2D to 3D culture systems for providing the cells with an architecture more similar to the physiological environment. Reproducing the three-dimensionality in vitro can guarantee beneficial effects in terms of cell growth, adhesion, proliferation, and/or their differentiation. Hydrogels have the same tailorable physico-chemical and biological characteristics as ECM materials. In this study, we propose a thermoresponsive chitosan-based hydrogel that gels thanks to the addition of organic and inorganic salt solutions (beta-glycerolphosphate and sodium hydrogen carbonate) and is suitable for cell encapsulation allowing obtaining 3D culture systems. Physico-chemical analyses showed that the hydrogel formulations jellify at physiological conditions (37 °C, pH 7.4), are stable in vitro up to three weeks, have high swelling ratios and mechanical stiffness suitable for cellular encapsulation. Moreover, preliminary biological tests underlined the pronounced biocompatibility of the system. Therefore, these chitosan-based hydrogels are proposed as valid biomaterials for cell encapsulation.